2002
DOI: 10.1108/02683940210423060
|View full text |Cite
|
Sign up to set email alerts
|

The “what”, “why” and “how” of spirituality in the workplace

Abstract: While the attention to workplace spirituality is growing, there is debate as to what exactly this term “spirituality” means. There seems to be multiple views of workplace spirituality. It could be argued that there are different definitions for the meaning of “spirituality” due to the very strong personal nature of the word itself. We argue that this multiple view of spirituality is a positive thing for organizations if managers attempt to understand differing spiritual views and also encourage all views withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
426
0
26

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(456 citation statements)
references
References 15 publications
4
426
0
26
Order By: Relevance
“…Recent studies and testimonies, such as the examples cited above, have suggested that workplaces that welcome whole people (people who express emotions alongside rational thinking) are globally more creative and engaging (Guillory, 2001;Krishnakumar and Neck, 2002). Yet compartmentalization is still seen as a necessity for business success (Lovell, 2002).…”
Section: Compartmentalization In Businessmentioning
confidence: 99%
“…Recent studies and testimonies, such as the examples cited above, have suggested that workplaces that welcome whole people (people who express emotions alongside rational thinking) are globally more creative and engaging (Guillory, 2001;Krishnakumar and Neck, 2002). Yet compartmentalization is still seen as a necessity for business success (Lovell, 2002).…”
Section: Compartmentalization In Businessmentioning
confidence: 99%
“…Burack (1999) indicated that when the employees recognized workplace spirituality, they would have pleasant feelings, which reinforced their problem-solving abilities, creativity, and increased organizational efficacy and financial benefits. Upon these statements, Krishnakumar and Neck (2002) inferred that when the employees recognize their workplace spirituality, their thinking would be expanded, which strengthened their intuition and creativity.…”
Section: Functions and Influences Of Workplace Spiritualitymentioning
confidence: 99%
“…Thus, they could reduce formal ethic regulations and criteria and the moral regulation costs of the organizations. In addition, upon literature review, Krishnakumar and Neck (2002) and Jurkiewicz and Giacalone (2004) inferred with precise logic and indicated that workplace spirituality would first positively influence the employees and increased organizational efficacy. The positive influences on the employees included an increase of stimulation, instinct, creativity, honesty, trust, self-realization, commitment, and improved adaptability, as elaborated below.…”
Section: Functions and Influences Of Workplace Spiritualitymentioning
confidence: 99%
See 1 more Smart Citation
“…It can also address existential crises and self-alienation caused by boring or repetitive work (Krishnakumar and Neck, 2002). Bell & Taylor (2003) suggest that spirituality at work is perceived as a reaction to negative influences on organizational life, such as work-life imbalance, downsizing and workaholism.…”
Section: Organizational Spirituality and Management Developmentmentioning
confidence: 99%